Menstrual pattern of severe intrauterine adhesion following hysteroscopy adhesiolysis - Salma, Umme (Bangladesh Journal of Medical Science, 2020)
Objective: The purpose of this study was to evaluate the menstrual and uterine shape in patients diagnosed with severe intrauterine adhesion (IUA) on hysteroscopy and to assess the outcome following hysteroscopic adhesiolysis. Materials and methods: It is a retrospective study of patients with severe intrauterine adhesion who attended with complain of infertility, abortion , and repeated dilatation and curettage to our institution from January 2017 and December 2017. Post hysteroscopic adhesiolysis the inserted of urinary balloon catheter and intrauterine device (IUD). The sodium hyaluronate gel was administered inside the uterus and oral cyclical hormonal treatment was initiated after the surgery to all patients to prevent reformationof adhesion, and promote endometrial regeneration respectively. The outcome of menstrual pattern and uterine shape were retrospectively analyzed. Data analyzed was performed with SPSS for Windows, version 20.0). Statistically signiﬁcant level was set at p<0.05. Results: In a total number of 64 patients with severe intrauterine adhesion and mean age of 30.1 years old were participated in this study. No identification of any complication around the hysteroscopy adhesiolysis. Out of 64 severe IUA patients, 59 (92.1%) patients had second, 42 (65.6%) had the third hysteroscopic adhesiolysis procedure required. After 3 months follow-up, restore of uterine shape and 95 % of patients in progress to normal menstruation, which was considered as significant (p<0.05). Conclusion: The patients with severe intrauterine adhesion (IUAs) have found significant progress of normal pattern of menstruation with normal shape of the uterine cavity following hysteroscopic adhesiolysis. The repeat procedure and strategies are necessary for prevention of adhesions. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.475-479